SURVEY CONCERNING STRENGTH PARAMETERS IDENTIFIED ON JUNIOR HANDBALL PLAYERS AND THE IMPORTANCE IN THE PRACTICE OF THE HANDBALL GAME AT THE PERFORMANCE LEVEL - ROHOZNEANU Mihai-Dan (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
In the theory and methodology of handball the concept of strength capacity is highlighted as part of physical training, and references are made and adapted to the game of handball. Determining the level of strength capacity in junior handball and analysis of responses to the questionnaire of handball coaches (who actively sought Strength development in handball at the junior level) will be practical and methodological foundation for organizing and conducting experimental research based on teaching. The research purpose is to achieve a preliminary study (questionnaire) regarding the development of the ability to strength the junior handball. Instructional strategy aimed at developing specific strength capacity in handball and it should have a well-defined and specified influence in the physical training of junior handball endpoints, intermediate lesson that must be met in order to increase the performance level of the players.